2019
DOI: 10.1002/aelm.201900754
|View full text |Cite
|
Sign up to set email alerts
|

Bromine Vacancy Redistribution and Metallic‐Ion‐Migration‐Induced Air‐Stable Resistive Switching Behavior in All‐Inorganic Perovskite CsPbBr3 Film‐Based Memory Device

Abstract: density, fast switching speed, multibit storage potential, and nonvolatile nature, is considered as one of the most promising candidate in nonvolatile memory field. [1][2][3] The RRAM device, with sandwich structure of top metal (TE)/ switching layer/bottom metal (BE), can be switched between a low resistance state (LRS) and high resistance state (HRS) under the stimulation of different voltage amplitudes or polarities. [4] Stable resistive switching (RS) behavior has been observed in various perovskite oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…After that, some solid electrolyte materials have been presented including Ag 2 Se [24], Ge 2 Sb 2 Te 5 [25], GeTe [124], etc. At present, a series of 2D materials such as graphene [89,125,126], molybdenum disulphide (MoS 2 ) [26,127,128] and perovskite materials (CH 3 NH 3 SnCl 3 and CsPbBr 3 ) [73,90] also inspired researchers' interest due to their small size, ultra-thin thickness and excellent physical properties, which have resulted in superior performance of RRAM devices. Chen et al proposed an electrode/oxide interface engineering technique by inserting single-layer graphene (SLG) into the TiN/HfO 2 /Pt RRAM device [89], which enabled the RESET current to be reduced by 22 times and the programming energy consumption reduced by 47 times.…”
Section: Thin Film Materials Of Rs Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…After that, some solid electrolyte materials have been presented including Ag 2 Se [24], Ge 2 Sb 2 Te 5 [25], GeTe [124], etc. At present, a series of 2D materials such as graphene [89,125,126], molybdenum disulphide (MoS 2 ) [26,127,128] and perovskite materials (CH 3 NH 3 SnCl 3 and CsPbBr 3 ) [73,90] also inspired researchers' interest due to their small size, ultra-thin thickness and excellent physical properties, which have resulted in superior performance of RRAM devices. Chen et al proposed an electrode/oxide interface engineering technique by inserting single-layer graphene (SLG) into the TiN/HfO 2 /Pt RRAM device [89], which enabled the RESET current to be reduced by 22 times and the programming energy consumption reduced by 47 times.…”
Section: Thin Film Materials Of Rs Mediummentioning
confidence: 99%
“…( e ) AlO x , reproduced from [ 19 ], with permission from Elsevier, 2020. ( f ) CsPbBr 3 , reproduced from [ 73 ], with permission from John Wiley and Sons, 2019. ( g ) Ge 2 Sb 2 Tr 5 , reproduced from [ 38 ], with permission from John Wiley and Sons, 2019.…”
Section: Figurementioning
confidence: 99%
“…5 c, the doublet peaks of Br 3 and Br 3 signals locate at 69.38 eV and 68.33 eV, respectively. Obviously, they shift toward the positive positions, indicating that V generate in the CABB layer [ 34 ]. In addition, as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5 a, the Br 3d peak is composed of a doublet with 3d 3/2 and 3d 5/2 signals at 69.38 and 68.33 eV. The Br 3d peaks of the CABB films slightly towards the positive, which indicated that abundant V Brs exists in the CABB film [ 28 ]. Figure 5 b shows the Bi 4f core-level spectrum.…”
Section: Resultsmentioning
confidence: 99%